Game changers : the story of Venus and Serena Williams - Cline-Ransome, Lesa; Ransome, James (New York : Simon & Schuster Books for Young Readers, 2018)
Shares the story of the sisters and tennis stars, including their special relationship as sisters and best friends, their constant training as children, and their incredible success in professional tennis.
School Library Journal starred, June 2018
Booklist starred, June 2015
Horn Book Starred, July 2018
Publisher's Weekly, June 2018
Bulletin (Center for Children's Books), June 2018
Kirkus Review, May 2018
Keywords: Williams, Venus, -- 1980- -- Juvenile literature; Williams, Serena, -- 1981- -- Juvenile literature; Tennis players -- Biography -- Juvenile literature; Tennis players -- Juvenile literature; Williams, Venus, -- 1980-; Williams, Serena, -- 1981-; Tennis players; African Americans -- Biography; Women -- Biography; Biographies; Nonfiction picture books